Improvement of the Preventive Measures for Managing Universiade-2013 Held in Kazan, Based on Comprehensive Evaluation of Epidemiological Risks as Regards Natural-Focal Infectious Diseases - S. K. Udovichenko; A. V. Toporkov; V. A. Safronov; I. G. Karnaukhov; N. V. Popov; V. P. Toporkov; V. V. Kutyrev (Проблемы особо опасных инфекций, 2013)
Presented is the methodology for comprehensive evaluation of epidemiological risks (spatial and temporal characteristics, risk factors and cohorts) associated with natural-focal infectious diseases that pose a threat to sanitary-epidemiological welfare of the population within the frames of Universiade-2013. The event has been characterized from the viewpoint of mass gathering taking into consideration the complex of related threats to sanitary-epidemiological welfare of the population. Analyzed has been regional epidemiological situation on the currently important infections, whereas natural-focal infections have been assessed in reference to epidemiological risk. Based on the comprehensive evaluation with GIS software application differentiated have been the territories against the level of potential epidemiological hazard, put forward has been methodological approach to non-specific prophylaxis of natural-focal infectious diseases. Discussed have been the fundamentals of the approach, herewith it has been demonstrated that justified selection of internal threat and identification of spatial risk factors, as well as nature, scope and timing of the preventive measures ensure provision of favorable epidemiological situation as seen in the case of Universiade-2013.